An experimental investigation of microexplosion in bio fuel emulsion - Khan, M.Y. (Asian Research Publishing Network, 2016)
Puffing and microexplosion characteristics of water in bio diesel emulsion droplets were investigated. Emulsified fuel droplets were visualized on a hot surface during Leidenfrost effect. The emulsions tested were with 9, 12 and 15 of water stabilized by 5, 10 and 15 of surfactant dosages with an HLB value of 6. The results show that the emulsion stabilized with 5 and 10 surfactant dosage undergoes microexplosion phenomenon, whereas emulsion with maximum surfactant dosage did not developed micro explosion. The puffing frequency was found to be increasing as the Sauter mean diameter of the dispersed water droplets in the emulsions decreased. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.